Approaches to Collective Cognition in the Historic Centre of Madrid: An Erasmus Interdisciplinary Experience - Mónica Alcindor; Waltraud Müllauer-Seichter; Sonia De Gregorio Hurtado; Leonor Medeiros; Mirella Loda; Delton Jackson (Land)
Beyond their direct use, buildings and heritage places are objects and settings which help to guide community actions. Cognitive perception systems interact directly with the built environment through action and generate experiences that will be used for subsequent actions. This requires a reorientation towards phenomenological perspectives that query the conceptual boundary between cognition and action. Five universities from three countries (Portugal, Italy, and Spain) came together in July 2023 through an Erasmus+ BIP (Blended Intense Programme) experience, developed for the La Latina neighbourhood, in the historical centre of Madrid. The intention was to highlight the importance of different disciplines, and interdisciplinary working, for planning an urban future which includes the goals of socio-economic and environmental sustainability, happiness, and the right of residents to maintain longstanding emotional connections with their neighbourhoods. The novelty of this experience compared to existing Master’s and PhD programmes in Europe was the early and intense contact of students with the subject through the development of fieldwork over two weeks. This was led by teachers from different disciplines to provide interdisciplinary perspectives for a training programme which included architecture, urbanism, urban anthropology, geography, history, and archaeology. Through this training, the intended outcomes were twofold: to equip students with the necessary knowledge and criteria to critically address these issues and to raise awareness among local stakeholders about the negative transformations affecting historic centres and their impact on residents’ quality of life.